Pursuing Happiness across Traditions: A Comparative Study of al-Ghazali in Kīmiyā’ al-Sa‘ādah and the Japanese Concept of Ikigai - Muhammad Afada Rifqiya; Abdullah Hosseinieskandian (Faculty of Ushuluddin and Philosophy, 2024)
Happiness is a universal goal that humans have pursued throughout history. This study compares the concepts of happiness according to Abū Ḥāmid al-Ghazālī in Kīmiyā’ al-Sa‘ādah and the concept of Ikigai in Japanese tradition. Using a descriptive qualitative approach, this study examines the similarities and differences between the two concepts based on text analysis and literature review. Al-Ghazālī emphasizes that true happiness is achieved through the purification of the soul, self-knowledge, and closeness to God. In contrast, Ikigai emphasizes the achievement of balance between personal satisfaction, social contribution, and life purpose. The results of this study indicate that both concepts are based on the importance of self-knowledge, building social relationships, and finding meaning in life as a path to happiness. The fundamental difference lies in their orientation: al-Ghazālī emphasizes the transcendental aspect of Allah, while Ikigai is more pragmatic in optimizing one’s potential in the world. This study underscores the importance of a holistic approach to happiness, which integrates spiritual values and everyday human life and opens the door to cross-cultural dialogue in understanding human well-being more comprehensively.